Biochemical studies on malathion resistance, inheritance and association of carboxylesterase activity in brown planthopper, Nilaparvata lugens complex in Peninsular Malaysia. - Abdul Latif, Mohamad; Omar, Mohd Yosuh; Tan, Soon Guan; Siraj, Siti Shapor; Ismail, Abdul Rahim (Institute of Zoology, Chinese Academy of Sciences, 2010)
Two sympatric populations of brown planthopper (BPH), one from rice and the other from Leersia hexandra were collected from each of five locations in Malaysia. All the tested malathion-resistant individuals of the rice BPH population and F1 generation (cross between malathion-resistant [usually caught on rice] and malathion-susceptible [usually caught on Leersia]) showed high esterase activity, while all malathion-susceptible individuals on L. hexandra showed low esterase activity. In the F2 generation,all the individuals tested against malathion were approximately 75% resistant and 25% susceptible and the inheritance pattern of esterase activity (high and low esterase activity) segregated in the same manner to a 3: 1 ratio. This confirms that resistance to malathion is mono-factorial and inheritance pattern of esterase activity is also linked to malathion resistance. Carboxylesterase or total esterase activity in BPH is inherited in a simple Mendelian fashion that is encoded by a single dominant gene. For the total esterase assay, average esterase activity levels in the rice-infesting population ranged from 17.64 to 19.37 nmoles1-napthol/mg protein while that in the Leersia-infesting population ranged from 5.29 to 6.11 nmoles 1-napthol/mg protein. In terms of esterase activity, the two sympatric Ni-laparvata lugens populations separated into two distinct groups. Results based on the tube color intensity test showed 96% and 98% resistant and susceptible individuals were present in the rice- and Leersia-infesting populations, respectively. In a filter paper test, the rice-infesting population had 94% with high esterase activity while the Leersia-infesting population had 96% with low esterase activity.